O conceito de gênero discursivo/textual em teses e dissertações que focalizam a produção textual em contexto de alfabetização (2010-2017) - Araújo, Elioenai Oliveira (2019)
The main objective of this research is identifying how the concept of discourse genre are constituted in theses and dissertations about textual production in the literacy context and in the initial three years of elementary school. Thus, we start with discussions about discursive genrer based on Mikhail Bakhtin (1997). In the presente thesis, we find to identify the contexts of speech development of theses and dissertations. Therefore we have tried to identify the genrer approach, objectives and problems of the academic works selected to make the research. And, we need to identify the theoretical references about discursive genres of theses and dissertations, and we try to understand how the concept of the discursive genres could contribute to the development of differente proposals - pedagogical strategies, methodological path to researche and results that dissertations and theses developed in the classroom. This thesis is bibliographic because we review database that was present in the Catalog of Thesis and Dissertations of the Coordination of Improvement of Higher Level Personal (CAPES). The treatment of the database was based on the reading steps proposed by Salvador (1980), and content analysis that was indicated by Bardin (2011). The research context needs to be observed in this thesis. The database collected to make the work was developed in the southeast of Brazil and focus on Education field. We verified different theoretical perspectives: philosophy of language, sócio-rethorique, socio-interactive and systemic-functional linguistics. The problems and objectives topics of the analyzed research, we could explain two different tendencies: gender as an instrument of teaching and as discourse. In the other hand, when we observe categorized surveys as a classroom, we also see two tendecies: genres as disciplinary content and genres as a concrete statement. Thus, we understand that textual gender concept followed two lines of approach, one focused on language in action, as a discourse, and another that focused the genres as an object of teaching.